Get the picture - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Picture supported communication in Africa: Fundamentals, examples and recommendations for appropriate communication processes in rural development programmes in sub-Saharan Africa By V Hoffmann, Margraf-CTA, 2000. 367 pp. ISBN 3 8236 1342 1 CTA number